2009
DOI: 10.1203/pdr.0b013e3181b9b48a
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Mizoribine on Cyclosporine A Nephropathy in Rats

Abstract: ABSTRACT:The therapeutic benefits of Cyclosporine A (CsA) are often limited by the chronic nephrotoxicity of its long-term use. Chronic nephrotoxicity is manifested by renal function impairment and progressive histopathological kidney lesions characterized by tubular vacuolization, tubular necrosis, interstitial fibrosis, and afferent arteriolopathy. This study tested the hypothesis that the concurrent administration of Mizoribine (MZR) may improve chronic CsA nephrotoxicity. Sprague-Dawley male rats were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…However, MZR has also been reported to have low clinical efficacy, as the sole immunosuppressant, for treating NS [19]. Interestingly, aside from its immunosuppressive effect, MZR also appears to have a beneficial effect against calcineurin inhibitors, CsA-induced intimal hyperplasia, and perivascular inflammatory cell infiltration in rat models [21,22]. Moreover, Takeuchi et al reported that MZR directly prevents podocyte injury in experimental puromycin aminonucleoside-induced nephropathy [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, MZR has also been reported to have low clinical efficacy, as the sole immunosuppressant, for treating NS [19]. Interestingly, aside from its immunosuppressive effect, MZR also appears to have a beneficial effect against calcineurin inhibitors, CsA-induced intimal hyperplasia, and perivascular inflammatory cell infiltration in rat models [21,22]. Moreover, Takeuchi et al reported that MZR directly prevents podocyte injury in experimental puromycin aminonucleoside-induced nephropathy [23].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MZR is used for the treatment of renal diseases including IgA nephropathy, nephrotic syndrome, lupus nephritis, and purpura nephritis, and is safe, reliable, and with acceptable efficacy. [8][9][10][11][12][13][14][15][16][17] As MZR increases the transcription activities of glucocorticoid receptors, 5,18 increases the efficacy of glucocorticoids, and reduce, the viral replication induced by long-term use of high-dose glucocorticoids, the present study investigated the efficacy of MZR in combination with moderate dose of glucocorticoids in treating patients with HBV-positive nephrotic syndrome. In the present clinical study, methylprednisolone, MZR, and entecavir were used as the combination treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Matsui et al (28) reported that MZR attenuates inflammatory response and macrophage infiltration against bleomycin-induced lung injury in mice. Recent reports previously indicated significant improvement in interstitial fibrosis and macrophage infiltration but no decrease in arteriolopathy and expression of TGF-β1 in CsA-treated rats after administration of MZR (6). Several studies have reported clinical improvement in histological arteriolopathy and renal allograft dysfunction with chronic CsA use as a result of the RAS blockade with either angiotensin-converting enzyme inhibitors or ARB.…”
Section: Mizoribine/arb For Csa Nephropathymentioning
confidence: 99%
“…Recent reports stated that concomitant administration of MZR significantly improved CsA-induced interstitial fibrosis and macrophage infiltration in CsA-treated rats. However, no decrease in arteriolopathy or expression of transforming growth factor (TGF)-β1 was observed after additional MZR administration in a model of CsA nephropathy (6).…”
mentioning
confidence: 99%